Evaluating the Utility of High-Resolution Computed Tomography of Thorax and its Correlation with Spirometric Indices in Patients with Emphysema-Predominant Chronic Obstructive Pulmonary Disease - Veena Keshuraj; Vijaya N. Holla; Tara Handattu; Mithun Rao (International Journal of Medicine and Health Development)
Background: High-resolution computed tomography (HRCT) is the preferred modality for identifying key morphological features of chronic obstructive pulmonary diseases (COPD), such as emphysema and chronic bronchitis. Objectives: To evaluate and identify the correlation between quantitative and qualitative HRCT features in patients with emphysema and various spirometric parameters. Materials and Methods: Seventy-five COPD patients presenting to the Department of Radiodiagnosis underwent thoracic HRCT scans. Tracheal index (TI), thoracic cage ratio (TCR), retrosternal distance (RSD), thoracic cross-sectional area/height2 (TCSA/ht2), vascular attenuation, vascular distortion, and directly visible small airways were evaluated. Correlations between these HRCT parameters and spirometric indices such as forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), Tiffeneau–Pinelli index (FEV1/FVC), and peak expiratory flow rate (PEFR) were determined. Results: Comparing HRCT parameters with spirometric indices revealed a significant direct correlation between TI and FEV1, FVC, FEV1/FVC, and PEFR (P < 0.05), and a significant inverse correlation between TCR1, TCR2, RSD, TCSA/ht2, and FEV1, FVC, FEV1/FVC, and PEFR (P < 0.05). Conclusion: HRCT provides regional anatomical information and can assess COPD airway abnormalities, regional gas trapping, and lung tissue structure alterations. HRCT features strongly correlate with spirometric indices, indicating its usefulness not only in diagnosing emphysema and its various subtypes but also in predicting the extent and severity of COPD.